Integration of Web-Based Key Booking and Monitoring System with Smart Key Rack for University Application - Idris, Farah 'Aini; Nurfarina Zainal, (Evolution in Electrical and Electronic Engineering, 2022)
This project introduces integration of the web-based key booking and monitoring system with smart key racks which have automated and real-time data collection that can vastly reduce key lost problems, and poor management systems. The key booking and monitoring system was developed by using IoT technology, which can be applied in the Faculty of Electrical and Electronic Engineering (FKEE) building. The webpage was developed using the Ionic Framework using Cloud Firestore to store the database. The smart key rack was developed by using Arduino IDE to program the NodeMCU ESP32, which controls the IR sensor, LCD, keypad, and solenoid lock to be integrated and work in parallel to the webpage. This key booking system allows the students and staff to book or cancel the reservation of the keys. The administrator can manage, monitor the keys, and verify the booking requests made by the users. This system will potentially minimise the inconvenience caused by manual key booking systems and improve the key management system at the university.